On algorithm complexity - Kudryavtsev, V. B.; Andreev, A. E. (Journal of mathematical sciences (New York, N.Y.), 2010)
This paper contains a review of the authors’ results in the theory of algorithm complexity. The results described concern methods for obtaining lower bounds (containing almost all exponential lower bounds on monotone complexity of monotone functions), synthesis of asymptotically optimal functional networks, minimization of Boolean functions, and the problem of solving Boolean equations.